A semiempirical dynamic model of reversible open circuit voltage drop in a PEM fuel cell. (11th July 2018) - Hu, Zunyan; Xu, Liangfei; Song, Ziyou; Li, Jianqiu; Ouyang, Minggao
Summary: Fuel cell voltage modeling is important for fundamental research. The main focus of previous studies has been the working voltage segment, whereas the accuracy of the open circuit voltage (OCV), especially the dynamic OCV change process, has been ignored. A semiempirical model including the OCV and an electrochemical model has been proposed in this study to clarify the reversible voltage drop process. A mixed cathode potential drop that is assumed as corresponding to a piecewise function relationship with an active surface area is introduced in this study. Fitting results exactly coincide with the original data in 2 modes, namely a quasistatic condition in a bench test and a dynamic condition in a fuel cell city bus. In the dynamic OCV drop process, the voltage drop due to the hydrogen crossover current approximately corresponds to 0.003 V and the mixed cathode potential drop approximately corresponds to 0.02 V.